Regular Functions with Values in Ternary Number System on the Complex Clifford Analysis. (22nd December 2013) - Kim, Ji Eun; Lim, Su Jin; Shon, Kwang Ho
Abstract : We define a new modified basis i ^ which is an association of two bases, e 1 and e 2 . We give an expression of the form z = x 0 +   i   ^ z 0 -, where x 0 is a real number and z 0 - is a complex number on three-dimensional real skew field. And we research the properties of regular functions with values in ternary field and reduced quaternions by Clifford analysis.